Propagation of lusala (Dioscorea hirtiflora), a wild yam, for in situ and ex situ conservation and potential domestication. (19th June 2020) - Zulu, D.; Ellis, R. H.; Culham, A.
Summary: Lusala ( Dioscorea hirtiflora Benth. subsp. pedicellata Milne-Redh) is an important wild edible tuber foraged widely from natural forests in Southern Zambia, but at risk from overharvesting and deforestation. Its propagation was investigated in glasshouse studies to explore potential domestication and future in situ and ex situ genetic resources conservation. Almost all tubers planted with visible shoot buds produced vines, with no effect of tuber size on vine emergence or tuber yield. Few tubers without visible shoot buds at planting produced vines, but those that did not re-tuberized. The progeny provided good vine emergence and similar tuber yield, with vines from tubers produced by re-tuberization being more vigorous. Re-tuberization in the absence of vine emergence also occurred in other experiments. Minisetts cut from the proximal end of tubers provided better vine emergence (with more from 20-mm than 10-mm-long sections) and greater tuber yield than mid- or distal minisetts. Nodal stem cuttings rooted well, vined, and provided small tubers. This study shows that lusala can be propagated successfully from tubers, minisetts, nodal vine cuttings, or mini-tubers from nodal vine cuttings, for genetic resources conservation and/or domestication. Domestication is likely to be hampered by the long period required for vines to emerge and establish. More sustainable foraging, including re-planting in natural forests, is recommended to balance consumption of lusala in the region and promote its long-term conservation.